Adutora Monsenhor Expedito: perdas, ampliação e integração - Castro, Tiago Elias Martins de (2018)
In the state of Rio Grande do Norte, about 60% of the population has as its source of drinking water supply system, a water source located beyond its territorial limits, and are supplied by the main pipeline systems. As a result of the long distances traveled by the water, witch still needs to overcome elevation gains, the costs of electric energy consumed by the elevator stations are significantly, referring to the operating costs of the systems. Water loss management combined with energy efficiency practices, together with continuous search for infrastructure projects with better efficiency, tend to reduce operating costs and ensure the sustainability of the systems. Considering the current characteristics of Monsenhor Expedito’s pipeline system, responsible for water supply in 30 inner-state cities, and the prerogatives of the new legal framework of sanitation, the present study intends to contribute to the system’s improvement through its precise diagnosis, regarding losses and energy cost, and evaluate alternatives of conception for its expansion, integrating to Armando Ribeiro Gonçalves’s water dam. The integration of systems allows scenarios of distribution with greater water security, while its infrastructure renovation would provide minimal operating costs.